Textbook biology (grade 10th) - Malik, jawad mohsin (National book foundation Lahore, 2011)
Biology Textbook for 10th Class provides a comprehensive introduction to key biological concepts, covering topics such as cells, ecosystems, and human anatomy, with clear explanations and engaging illustrations for young learners.